PENGARUH INOVASI PRODUK BARU, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PC TABLET APPLE iPad (STUDI KASUS PADA MAHASISWA PENGGUNA iPAD DI FISIP UNDIP SEMARANG) - Aleiyya, Ihda La; Waluyo, Handoyo Djoko; Widayanto, Widayanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
PC Tablet Apple iPad is a tablet made by the Apple Inc. Tablet is sort of electronic device that looks like a regular smartphone, but with larger screen than the common smartphone. The difference tablet with the smartphone is that tablet didn't have telephony function as well short message service that usually embedded with cellphone. Apple Inc. produces many things, from smartphone until internet router, and iPad is one of the thing that bridging the gap between their smartphone, known as iPhone, to their own personal computer operating system, known as Mac OS. Producer hoping that iPad would simplify the user to do their needs that can't be executed by iPhone and the user didn't have to bother to operate their PCs. This research used explanatory research characteristic, with 100 respondents whose possess Apple iPad. This research also used non probability sampling technic particularly purposive sampling. Analysis technic used are validity test, reliability test, simple regression linear, double regression linear, T test, and F test with SPSS 21.0. From the research conclusion can be learned that product innovation, brand image and price have impact on the purchasing decision. The improvement of product innovation, brand innovation and price would improve the purchasing decision. This research suggests improving product innovation with consumer oriented value, which is provides more diverse features, maintainning brand image that Apple have already achieved, with the objective to survive market pressure from other products, and the last thing is affordability of price to acquire broader market to reduced market shifting probability and improve purchasing decision.